Outpatient bendamustine and idarubicin for upfront therapy of elderly acute myeloid leukaemia/myelodysplastic syndrome: a phase I/II study using an innovative statistical design. (18th April 2014) - Lionberger, Jack M.; Pagel, John M.; Sandhu, Vicky K.; Xie, Hu; Shadman, Mazyar; Mawad, Raya; Boehm, Alexandra; Dean, Carol; Shannon‐Dorcy, Kathleen; Scott, Bart L.; Deeg, Hans Joachim; Becker, Pamela S.; et al.
Summary Combinations of agents may improve outcomes among elderly acute myeloid leukaemia (AML) and high‐risk myelodysplastic syndrome (MDS) patients. We performed an adaptive phase I/II trial for newly‐diagnosed AML or high‐risk MDS patients aged ≥50 years using a Bayesian approach to determine whether 1 of 3 doses of bendamustine (45, 60, 75 mg/m2 days 1–3), together with idarubicin (12 mg/m2 days 1–2), might provide a complete response (CR) rate ≥40% with <30% grade 3–4 non‐haematological toxicity. We treated 39 patients (34 AML; five MDS with >10% marrow blasts; median age 73 years). None of the three bendamustine doses in combination with idarubicin met the required CR and toxicity rates; the 75 mg/m2 dose because of excess toxicity (two of three patients) and the 60 mg/m2 dose because of low efficacy (CR rate 10/33), although no grade 3–4 non‐haematological toxicity was seen at this dose. Median survival was 7·2 months. All patients began treatment as outpatients but hospitalization was required in 90% (35/39). Although we did not find a dose of bendamustine combined with idarubicin that would provide a CR rate of >40% with acceptable toxicity, bendamustine may have activity in AML/MDS patients, suggesting its addition to other regimens may be warranted.